EXPOSURE TO CARCINOGENIC ENVIRONMENTAL POLLUTANTS IN A LARGE INDUSTRIAL CENTER AS A FACTOR FOR FORMING CHRONIC HYPERPLASTIC LARYNGITIS - Осипов, Виктор Дмитриевич; Суржиков, Дмитрий Вячеславович; Кислицына, Вера Викторовна; Штайгер, Варвара Адамовна (Medicine in Kuzbass, 2019)
Objective – the purpose is studying the influence of anthropogenic environmental factors on the development of clinical manifestations of chronic hyperplastic laryngitis in industrial workers. Materials and methods. The susceptibility of workers to chronic laryngitis was studied (19 parameters of peripheral blood of cellular and humoral immunity). Phagocytic and cytochemical activity of neutrophilic leukocytes was studied in the subjects examined. An assessment of aerogenic carcinogenic risk for individuals living within the industrial center has been carried out. Results. The individual carcinogenic risk related to the concentration of carcinogenic substances ranges from 1.52 × 10-4 to 1.84 × 10-4 in the air of the industrial center. The value of inhalation carcinogenic risk exceeds the acceptable level of risk by 1.522-1.84 times (depending on the year of observation). Treatment of the patients with chronic hyperplastic laryngitis and leukoplakia gave good results and the malignancy of the process with dynamic observation for 5 years and longer was not observed. After the treatment, the indicators of cellular and humoral immunity, as well as tumor markers did not differ from the data of healthy individuals. Conclusions. The formation of larynx pathology in the conditions of an industrial city is due to the priority effect of atmospheric pollution with soot and formaldehyde. The research results allow recommending more widespread use of preventive inhalations among industrial workers, which reduces the risk group for laryngeal incidence.